Singing as a Handicap: The Effects of Food Availability and Weather on Song Output in the Australian Reed Warbler Acrocephalus Australis - Berg, Mathew L.; Beintema, Nienke H.; Welbergen, Justin A.; Komdeur, Jan (Journal of Avian Biology, 2005)
Bird song is generally regarded as a sexually selected trait, and may represent a reliable handicap signal under at least certain conditions. Females may use the degree of male song production as a reliable cue to male condition or territory quality. We investigated the effect of supplementary feeding on song output in the migratory Australian reed warbler Acrocephalus australis. We experimentally increased the food availability on alternate days, and recorded several weather variables. We measured song rate and song length independently. Supplementary fed birds sang more on feeding days than on non-feeding days, while control birds did not show this effect. Song output was not significantly associated with any of the weather variables examined. Our results indicate that singing has the potential to serve as a reliable handicap signal to territorial food availability irrespective of the prevailing weather conditions. We discuss the role of energetic constraints and behavioural flexibility on the signaling function of song.
Keywords: food; weather; Acrocephalus australis